A Case Study Of Public Bank Berhad - Gopalan, Ganapathy (2004)
This paper looked at all the possible areas in order to evaluate Public Bank Berhad's strengh and weaknesses.Based on the study done, overall asset quality indicators are well within manageable limits and continue to be favorable compared too many peer banks. This reflects Public Bank's high underwriting standards and conservative reserving policies. Public Bank is also well positioned to meet the challenges and seize the opportunities to benefits from the stronger economic growth.